2010
DOI: 10.1590/s1984-82502010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of administering testosterone undecanoate in rats subjected to physical exercise: effects on the estrous cycle, motor behavior and morphology of the liver and kidney

Abstract: The aim of the work was evaluate the effects of testosterone undecanoate (TU) treatment combined with moderate physical training on: the estrous cycle, body weight (BW), motor behavior (MB), and the morphohistology of the reproductive system, the liver and kidney in rats. Female Wistar rats (180 g -250 g) were divided as follows: sedentary + TU (S + TU), trained + TU (T + TU), sedentary + vehicle (S + V), trained + vehicle (T + V). The rats swam 50 min/Day, strapped with a 5% BW load, for 4 weeks. During this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
2
14
0
1
Order By: Relevance
“…This was in agreement with another study, who studied the effects of testosterone undecanoate (TU) treatment reported degeneration of the kidney were found in 25% of the animals treated with TU [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with another study, who studied the effects of testosterone undecanoate (TU) treatment reported degeneration of the kidney were found in 25% of the animals treated with TU [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…In the groups treated with highest doses, the ovarian weight remained unchanged. It is well documented that the AAS promotes reduction in reproductive organ weights (Camargo et al 2009a(Camargo et al ,b, 2014Bento-Silva et al 2010;Karbalay-Doust & Noorafshan 2012). The suppression of estrous cyclicity caused by AAS treatment was previously reported in various studies (Gerez et al 2005;Mobini Far et al 2007;Bento-Silva et al 2010;Camargo et al 2011Camargo et al , 2014Chuffa et al 2011b) and severely affects the sexual cycle of women (Maravelias et al 2005).…”
Section: Discussionmentioning
confidence: 88%
“…The first injection was administered at the estrus phase of the cycle in all animals. The CD group was used in this study based on previous reports that AAS treatment promotes persistent diestrus (Camargo et al 2009a,b;Bento-Silva et al 2010;Chuffa et al 2011b). In this regard, the evaluation of ovarian tissue was carried out in a specific stage of the estrous cycle that androgenized females persisted or maintained for a long time during the experimental period.…”
Section: Experimental Designmentioning
confidence: 99%
“…The estrous acyclicity promoted by the treatment of ND is widely reported (Clark et al., ; Gerez et al., ; Mobini Far et al., ; Camargo et al., ,; Bento‐Silva et al., ; Chuffa et al., ), and this effect is related to a disruption of the neuroendocrine functions, in which high levels of exogenous testosterone alter the release of the Follicle stimulating hormone (FSH), Luteinizing hormone (LH), estrogen, and progesterone (Strauss et al., ; Gao and Short, ; Bronson et al., ; Blasberg et al., ). The persistence in diestrous found in ND‐treated animals and after 30‐day recovery indicate that nandrolone is slowly released from the injection site into the blood circulation with a half‐life of 6 to 8 days (Van der Vies, ), since it is a fat‐soluble substance that produces sodium retention by the kidneys before being excreted.…”
Section: Discussionmentioning
confidence: 99%